Cover Picture: Comparing Ullmann Coupling on Noble Metal Surfaces: On‐Surface Polymerization of 1, 3, 6, 8‐Tetrabromopyrene on Cu(111) and Au(111) (Chem. Eur. J. 17/2016). Issue 17 (16th March 2016) - Pham, Tuan Anh; Song, Fei; Nguyen, Manh‐Thuong; Li, Zheshen; Studener, Florian; Stöhr, Meike
Abstract : The influence of the metal surface (Cu vs. Au) on the on‐surface polymerization reaction of 1, 3, 6, 8‐tetrabromopyrene was investigated in detail. Not only could the catalytic role of the underlying substrate for the debromination reaction be revealed, but also it was found that the chemical nature of the chosen substrate influences the formation of intermolecular bonds leading to structurally different polymer networks. More information can be found in the Full Paper by T. A. Pham, M. Stöhr et al. onpage 5937 ff.